2014
DOI: 10.7863/ultra.33.8.1485
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of the Medial Ulnar Collateral Ligament Distal Ulnar Attachment

Abstract: We have successfully shown that the distal ulnar attachment of the MUCL can be visualized on high-resolution sonography. This preliminary work provides a framework for developing protocols for diagnosis of injuries to the distal ulnar collateral ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In this study, length of the ulnar footprint measured an average of 29.2 mm. Others have found similar lengths when appreciating a tapered insertion with means of 30.2 mm and 29.2 mm[ 21 , 22 ]. Further study by Camp et al[ 18 ] identified a tapered insertion with a mean surface area of 187.6 mm 2 and an ulnar footprint length averaging 29.7 mm.…”
Section: Anatomymentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, length of the ulnar footprint measured an average of 29.2 mm. Others have found similar lengths when appreciating a tapered insertion with means of 30.2 mm and 29.2 mm[ 21 , 22 ]. Further study by Camp et al[ 18 ] identified a tapered insertion with a mean surface area of 187.6 mm 2 and an ulnar footprint length averaging 29.7 mm.…”
Section: Anatomymentioning
confidence: 81%
“…These lengths were measured from the center of the origin to center of sublime tubercle, based on a direct insertion onto the sublime tubercle without a distal extension. In contrast, more recent reports measured from the center of the humeral origin to the most distal point of tapered insertion reported mean lengths of 53.9 mm[ 21 ] and 51.7 mm[ 22 ]. The difference in length measured between a non-tapered sublime insertion and a tapered insertion calls for further study to evaluate native AB anatomy and the clinical relevance of different measurements.…”
Section: Anatomymentioning
confidence: 99%
“…First, anatomic and biomechanical studies suggest that higher elbow flexion angles may tension the portion of the UCL imaged during this investigation [37‐40]. The anterior bundle of the UCL originates from the flat, anteroinferior surface of the medial epicondyle and inserts broadly over the sublime tubercle and proximal ulna [2,22,37‐42]. Sonographically, the most distinct region of the UCL has been shown to be the anterior band of the anterior bundle, which is most taut from 60° to 90° of flexion [9,10,16].…”
Section: Discussionmentioning
confidence: 94%
“…When measuring CSA, the distal perimeter of the UCL was considered to be the sublime tubercle. Although the long ulnar attachment of the UCL was visualized in all cases, as recently described, this portion of the UCL was excluded from CSA measurements because of its long, thin structure and unclear clinical significance [2,22].…”
Section: Methodsmentioning
confidence: 93%
“…In previous studies ( Table 3 ), § morphological features of the AB and PB were not consistent. This is because limb positions at the time of measurement have included the elbow joint in extension with the forearm in supination, 3 , 19 elbow flexion at 25°, 15 elbow flexion at 90°, 9 maximum tension position, 28 maximum tension position in neutral position of the forearm, 1 neutral position of the forearm, 10 and even undescribed positions 2 , 16 - 18 , 22 , 30 , 32 , 33 , 35 that presumably varied widely among studies. In addition, the AB is generally measured as a single bundle originating from the anteroinferior aspect of the medial epicondyle of the humerus and inserting at the sublime tubercle of the ulna.…”
Section: Discussionmentioning
confidence: 99%